2021
DOI: 10.1177/10998004211029044
|View full text |Cite
|
Sign up to set email alerts
|

Increased Systolic Blood Pressure Mediates the Relationship Between Urate and Gout Risk in Indonesia: A Novel Application of a Partial Least Squares-Structural Equation Model

Abstract: Background: Most Indonesians with hyperuricemia are less than 40 years old, which suggests an increasing gout risk in the country. Meanwhile, untreated hyperuricemia was also suggested to lead to hypertension. Yet, it is unclear whether blood pressure (BP) plays a mediating role between urate and gout. Objective: We investigated the mediating effect of BP between urate and gout risk in Indonesians using a partial least squares-structural equation model. Method: A community-based retrospective case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Hence, by considering hereditary characteristics and their interactions with environmental factors, these findings indicate that gout appears to be a serious public health issue in Indonesia (Kurniasari, et al, 2021b). This evidence shows that gout contributes to clinical impacts and highlights the necessity for more studies into effective gout therapy management (Kurniasari, et al, 2021a).…”
Section: Gout Prevalence In Indonesiamentioning
confidence: 86%
See 2 more Smart Citations
“…Hence, by considering hereditary characteristics and their interactions with environmental factors, these findings indicate that gout appears to be a serious public health issue in Indonesia (Kurniasari, et al, 2021b). This evidence shows that gout contributes to clinical impacts and highlights the necessity for more studies into effective gout therapy management (Kurniasari, et al, 2021a).…”
Section: Gout Prevalence In Indonesiamentioning
confidence: 86%
“…In the same circumstances, based on global racial comparisons, Indonesians have a higher gout risk due to the interplay between heredity and environmental factors which have led to high prevalence of hyperuricemia and gout in Indonesia (Kurniasari, et al, 2021b). Currently there are no guidelines for diagnosing and treating gout in Indonesia; consequently, general practitioners might treat gout patients differently (Kurniasari, et al, 2021a).…”
Section: Gout Prevalence In Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term use of diuretics may cause the human body to increase uric acid levels by increasing uric acid reabsorption and decreasing uric acid excretion, or by increasing the production of uric acid, thus inducing hyperuricemia, which in turn might potentially lead to the development of gout. However, some studies have also found that when adjusted for some variables, the positive association between hypertension and gout risk was not signi cant [32]. It should be noted that the inconsistent associations observed in these routine clinical studies are at least partially attributed to differences in sample size, reverse causality, and cultural, dietary, socioeconomic status, lifestyle, and genetic differences between populations at sampling sites that cannot fully mitigate confounding effects.…”
Section: Hypertension and Goutmentioning
confidence: 96%
“…Likewise, a survey study among 4683 adults conducted in a rural area of Java Island, Indonesia, reported prevalences of gout and hyperuricemia in men of 1.7% and 24.3%, respectively. In a global ethnic group comparison, Malayo-Polynesian males had higher rates of gout and hyperuricemia than Caucasian men (Darmawan, 1992; Dyah Kurniasari et al, 2021). Another study also reported that gout is a common arthritic illness in Malayo-Polynesian people (Kurniasari et al, 2021; Padang et al, 2006), and Indonesians are included in the Malayo-Polynesian ethnic group (Klamer, 2019).…”
mentioning
confidence: 99%